Combination of Red Betel (Piper crocatum) Leaf and Sambiloto (Andrographis paniculata Ness) Herb Extract on Reduction of Lipid Profile in Diabetic Rats - Tjahjono, Kusmiyati; Rahmawati, Nesti; Afifah, Diana Nur; Kinasih, Larasati Sekar (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aims to determine the antihyperlipidemic effect of a combination of red betel extract and sambiloto herb in an experimental animal model of Type 2 Diabetes Mellitus (T2DM). This study was a randomized pre-post-test experiment with a control group design on 25 male Sprague-Dawley rats. Rats experienced T2DM with a high-fat diet for 14 days and Streptozotocin (STZ) induction of 55 mg/kgBW preceded by nicotinamide (NA) 100 mg/kgBW. We confirmed T2DM if the rats' fasting glucose levels were less than 200 mg/dl. The rats were randomly divided into 5 groups: negative control (K1), positive control (K2), combination of red betel leaf and sambiloto herb extract 75:25 (P1), 50:50 (P2), and 25:75 (P3). The combination of red betel leaf and sambiloto herb extract at any dose was able to significantly reduce total cholesterol, LDL cholesterol, and triglyceride levels (p<0.05). The combined extract of red betel leaf and sambiloto herb at a ratio of 75:25 yielded the effective dose for reducing total cholesterol, triglyceride levels, and LDL. In T2DM rats, the combination of these extracts has the potential to increase total cholesterol, LDL, and triglyceride levels.